2003
DOI: 10.1007/s00134-002-1601-2
|View full text |Cite
|
Sign up to set email alerts
|

PIM2: a revised version of the Paediatric Index of Mortality

Abstract: PIM2 has been re-calibrated to reflect the improvement that has occurred in intensive care outcome. PIM2 estimates mortality risk from data readily available at the time of ICU admission and is therefore suitable for continuous monitoring of the quality of paediatric intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
714
2
23

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 973 publications
(752 citation statements)
references
References 16 publications
13
714
2
23
Order By: Relevance
“…The patients were categorized according to their age, gender, mortality risk rate prognosis by admission (using the PIM II prognosis score) (18) ; admission diagnosis, degree of kidney injury (pRIFLE) during the hospitalization, mechanic ventilation (MV) need, vasoactive drugs (VD) need, nephrotoxic drugs (ND) exposure, peritoneal dialysis (PD) need, time of stay in days (HD) and outcome (either discharge or death).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients were categorized according to their age, gender, mortality risk rate prognosis by admission (using the PIM II prognosis score) (18) ; admission diagnosis, degree of kidney injury (pRIFLE) during the hospitalization, mechanic ventilation (MV) need, vasoactive drugs (VD) need, nephrotoxic drugs (ND) exposure, peritoneal dialysis (PD) need, time of stay in days (HD) and outcome (either discharge or death).…”
Section: Methodsmentioning
confidence: 99%
“…In pediatrics, the most used prognostic indicators are PRISM (Pediatric Risk Index Score for Mortality) and PIM (Pediatric Index of Mortality). (17,18) The AKI diagnosis methods include: clinical evaluation of the urinary output and laboratory tests as urinalysis, blood urea nitrogen, and creatinine, however with low sensitivity and specificity. (19) Biomarkers for early AKI detection are currently under investigation, among them neutrophil gelatinase associated lipocalin (NGAL), cystatin C, interleukin 18, and kidney injury molecule-1 (KIM-1).…”
Section: Introductionmentioning
confidence: 99%
“…It is a measure of the likelihood of dying during the PICU admission (Slater et al, 2003). It is useful to compare different systems of intensive care and for describing severity of illness for groups of patients in research studies.…”
Section: Paediatric Index Of Mortality (Pim2)mentioning
confidence: 99%
“…4 The principal scores that have been developed for the pediatric population are the PRISM (Pediatric Risk of Mortality) 5 and PIM (Paediatric Index of Mortality), 6 with their most recent versions being PRISM III 7 and PIM-2. 8 These scores were developed by identifying variables relevant to mortality risk and scoring them after a multivariate statistical analysis by logistic regression. 9 The PRISM score was published in 1988 by Pollack et al and exhibited an excellent discriminatory and predictive performance.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several articles that have evaluated the PIM have shown that is performs well at predicting death. [11][12][13][14][15][16] In 2003 the PIM Study Group published a revised version of the PIM, the PIM-2 16,17 which, compared with the original version, 18 is supposed to be better calibrated, safer and better adjusted for varying diagnostic groups. This new version has not yet been evaluated independently and more information is necessary with respect of its performance in other regions and, because it was published after this study began, it was not investigated.…”
Section: Introductionmentioning
confidence: 99%